2003
DOI: 10.3168/jds.s0022-0302(03)73788-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Traffic Situations on the Behavior and Performance of Cows in an Automatic Milking System

Abstract: Two cow traffic situations were tested sequentially in an automatic milking system (AMS) for effects on cow behavior, effective use of the barn, and milking capacity. The first situation was forced cow traffic: 63 cows had to pass through the AMS to go from the lying area to the feeding area. The second was semiforced cow traffic: 67 cows (60 cows from before) had free access to a forage feeding area at one end of the barn but could only access an area with concentrate feeders by passing through the AMS. Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…Although one cow entered the AMS voluntarily at the first day of milking, the rate of voluntary visits did not achieve levels of more than 90% until d 9 of AMS milking. The rate of voluntary visits dafter successful adaptation to AMS Days in milk Relative milk yield (%) milking corresponds to previous investigations in adapted cows (Winter and Hillerton, 1995;Ketelaarde Lauwere et al, 1998;Hermans et al, 2003;Harms and Wendl, 2004). However, it has to be pointed out that this level was not approached until d 9 of AMS milking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one cow entered the AMS voluntarily at the first day of milking, the rate of voluntary visits did not achieve levels of more than 90% until d 9 of AMS milking. The rate of voluntary visits dafter successful adaptation to AMS Days in milk Relative milk yield (%) milking corresponds to previous investigations in adapted cows (Winter and Hillerton, 1995;Ketelaarde Lauwere et al, 1998;Hermans et al, 2003;Harms and Wendl, 2004). However, it has to be pointed out that this level was not approached until d 9 of AMS milking.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore several approaches to attract an AMS visit have been intensively studied (Winter and Hillerton, 1995;Ketelaar-de Lauwere et al, 1998;Hermans et al, 2003;Harms and Wendl, 2004).…”
mentioning
confidence: 99%
“…However, the effects are likely to be even more severe in dairy farms with an AMS since the success of these systems depends on the cows voluntarily visiting the milking unit a sufficient number of times. A reduction in visits to the milking unit as a result of lameness could be expected to influence feeding frequency (Melin et al 2005), grazing time (Spo¨rndly and Wredle 2004) use of lying stalls (Hermans et al 2003) and milk composition (Nielsen et al 2005), especially where forced traffic is used. Although our sample cows were not a random sample of the herds, we found that about 20% of the cows were slightly or severely lame, which corresponds more-or-less to the estimates of prevalence reported in North American dairy farms (e.g., Espejo et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…O robô deve ser projetado para permitir um tempo ocioso adequado para a limpeza do sistema de um animal para outro visando evitar a contaminação de animal para animal. Salas de espera que possuem saídas podem ser construídas para evitar competição na entrada da ordenha (HeRMans et al, 2003).…”
Section: Funcionamento Da Ordenha Robo-tizadaunclassified